A patient with an ectopic sphenoid bone TSH secretory adenoma: Case report and review of the literature - Kumar, Shejil; Phang, Cun An; Ni, Huajing; Diamond, Terrence (Frontiers in Endocrinology, 2022)
Ectopic thyroid stimulating hormone (TSH)oma is exceedingly rare and can be associated with significant diagnostic delay. Clinical presentation depends on anatomical locationand size of the ectopic tumour and degree of thyrotoxicosis. A 71-year-old female presented with goitre and thyrotoxicosis. Initial investigations revealed elevated free thyroxine (fT4) and tri-iodothyronine (fT3) with inappropriately high-normal TSH. Assay interference was unlikely, pituitary magnetic resonance imaging (MRI) scan was reported as ‘normal’ and germline sequencing was negative for thyroid hormone receptor ß pathogenic variants. One-year later, total thyroidectomy for enlarging symptomatic goitre and suspicious nodule revealed multifocal microscopic papillary thyroid carcinoma. Six-years later, she presented to an ear, nose and throat surgeon with nasal congestion and a sphenoid bone mass was discovered on naso-endoscopy and imaging. Ectopic TSHoma was confirmed on surgical resection and review of the initial pituitary MRI scan revealed the mass which had initially been missed. This is the first reported case of an ectopic TSHoma located in the sphenoid bone. Ectopic TSHoma should be considered in patients with inappropriate TSH secretion when more common differentials are excluded including thyroid hormone resistance or pituitary TSHoma.